Formação contínua: caminhos e descaminhos - Soares, Luciane Souza (2007)
This research, which comes from a voluntary project that investigates the development of a cooperative process between two teachers at a kindergarten public school (Escola Municipal de Educação Infantil EMEI), wishes the cooperative and reflexive construction of the senses about the meanings related to professional work, focusing on the preparation of chores with students, in contexts that make them comprehend their actions, inserting transformations and the cooperative building of knowledge. The research was based on the perspective of the socio-historical and cultural activity theory (Vygotsky, 1934/1936, 1934/2002, 19830/2002; Leontiev, 1977/2003, 1959/1998; Enfeström, 2003, 2002, 1999, 1987). The speech was prepared through the dynamism of this perspective, inserted on a collective activity system, in which the subjects attribute senses to the meanings related to the fact of been a teacher at a public school (EMEI) and taking different places in uses of the language. This study is based on theorist presupposes of Brookfield (1987), Freire (1970), Giroux (1997), Morales (1998) that discuss ways of teaching and developing the critical thinking, having the questions as an instrument of semiotic meditation in the development of a critic professional. This study is cooperativebased (Magalhães, 1998/2002; Liberali, 1999/2002), due to the fact that this is an investigative process that aims the observation, intervention, and analysis of transformations (or not) in the pedagogical practice of the participants. The discussion of the data is based on the theory of the activity, focusing on the description of the systems and the analysis of the speech, with basis on Kerbrat- Orecchioni (1996), which admires the principles that react to the system of conversation turns, the horizontal and vertical relations in the notion of politeness. The discussion of the results revealed that the reflexive job accomplished in eight programmed sessions, presented here, created the transformation of the teaching-learning conception of the teacher, that was, at first, afraid of and had difficulties in working with real potential of the kids, limiting their activities to the mere copy of letters, syllables and words. After the end of this study, it was realized a change in the teacher s behavior, in the sense of been able to work with texts, valuing the cultural knowledge of the group/ class and, specially, identifying its job as a mediate element and an interactive maker among the students and the latter with aims of knowledge. The results point, also, to the transformation related to the perception that the importance of the teacher is to create another transformation that deals with respect to the perception that the teacher s aim is wider than a simple repetition. The teacher s intention is to broaden the repertory of each child, allowing the trade of information and experiences among them and, furthermore, allowing the contact with art made by men throughout history